TOTAL PHYSICAL RESPONSE- STORYTELLING Salah Satu Pendekatan Komunikatif pada Pembelajaran Bahasa Inggris Bagi Anak Usia Dini - Failasofah Failasofah (Universitas Batanghari Jambi, 2009)
Everyone might agree with the statement ‘learning is an activity that starts at birth and can be expected to continue for a lifetime’. In learning, children are not a miniature of adult, they have their own world, means that they do not learn things exactly the same way adults do. More specifically, children have their own culture and learning preferences. That is, children learn by way of physical activities (i.e., hands on experiences) in the context of doing things embedded in their daily lives, both individually and socially. Total Physical Response-Storytelling (TPR-S) provides other benefits over traditional approaches to foreign language teaching. Through consistent and comprehensible exposure to grammatically-correct language, students develop an